The effect of porous zigzag-type breakwaters on the coastline changes in Neuheun village, Aceh. Issue 1 (September 2020) - Pagihariadi, P; Fatimah, E; Syamsidik, S
Abstract: The process of changing the coastline has always been a challenge for coastal communities. Beach erosion has been a threat with the coastline withdrawing from its previous position. Coastal protection buildings are needed to overcome coastal erosion problems, and alternative construction also needs to be developed. The zig-zag type porous breakwater is quite effective in reducing erosion based on several small-scale physical models that have been developed. Therefore a prototype was built and tested to observe its usefulness, and how it was applied in the field. This study aims to assess the effect of installing zigzag type porous breakwaters on coastline changes. This research began with the installation of construction and continued with observing changes in the coastline. Observations are carried out periodically at any time, to see changes in the contour of the beach that occurs. Observations were made by leveling the beach surface against several transverse profiles. Changes in coastline due to construction will be analyzed by looking at the relation to the wind direction. The results obtained from several observations show that the construction of a zig-zag type porous breakwater has a positive effect in reducing erosion, as long as the breakwater distance with the coastline does not exceed the breakwater length.